Humans of New York : a alteridade ressignificada a partir das redes sociais - Pechansky, Rafaela Chiapin (2018)
This work aims to understand how the concept of alterity is being ressignified through the digital environment in the contemporary world. The subject of this research is the page Humans of New York. The selected corpus for interpretation (collected throughout 2016 and 2017 and made by 20 posts) is focused on (1) posts that frame immigrants and (2) public manifestations through likes/reactions and comments. For contextualization, a few concepts are discussed, such as internet, social networks, algorithms and filter bubbles. The theme of otherness, then, is placed in perspective, among concepts just as identity, hospitality and anthropology of emotions. The method used is Deep Hermeneuthics, of Thompson, combined with digital methods. The data found indicates that people are conditioned to digital features at the same time as they appropriate a new environment, which impacts fundamentally the way we relate to the Other.